Limited Sensitivity of Serum Alkaline Phosphatase as an Early Biomarker of Acute Hexavalent Chromium Toxicity - Rena, Normasari; Icha, Nadhirotul Izza Afida; Alvin , Alfaaros; Al Munawir (Jember Medical Journal, 2026)
Hexavalent chromium [Cr(VI)] is a highly toxic heavy metal widely used in industrial processes and known to induce multi-organ toxicity. Serum alkaline phosphatase (ALP) is commonly used as a biochemical marker of hepatobiliary and bone dysfunction; however, its sensitivity in detecting early acute Cr(VI) toxicity remains unclear. This study aimed to evaluate serum ALP as an early biomarker of acute hexavalent chromium toxicity in Wistar rats following short-term oral exposure to chromium trioxide (CrO₃). This experimental study employed a post-test-only control-group design with 30 maleWistar rats randomly divided into three groups (n = 10/group): a control group receiving distilled water, a low-dose group receiving CrO₃ at 1 mg/kgBW, and a moderate-dose group receiving CrO₃ at 5 mg/kgBW. Treatments were administered orally for seven consecutive days. Blood samples were collected on day 8, and serum ALP levels were measured using an enzymatic spectrophotometric method at 405 nm. Data were analyzed using one-way ANOVA with a significance level of p < 0.05. Mean serum ALP levels were 236.28 ± 39.46 U/L in the control group, 208.62 ± 50.90 U/L in the 1 mg/kgBWgroup, and 205.20 ± 42.86 U/L in the 5 mg/kgBW group. Although both CrO₃-treated groups showed lower mean ALP levels than controls, statistical analysis revealed no significant difference among groups (p = 0.225). In conclusion, acute oral exposure to Cr(VI) at doses of 1 mg/kgBW and 5 mg/kgBW for seven days did not significantly alter serum ALP levels in Wistar rats. These findings suggest that serum ALP has limited sensitivity as an early biomarker of acute hexavalent chromium toxicity.